Caffeine Protects Dopaminergic Neurons From Dopamine-Induced Neurodegeneration via Synergistic Adenosine-Dopamine D2-Like Receptor Interactions in Transgenic Caenorhabditis elegans - Manalo, Rafael V. M.; Medina, Paul M. B. (Frontiers in Neuroscience, 2018)
Previous studies have suggested that caffeine reduces the risk of L-DOPA-induced dyskinesia. However, caffeine is also known to promote dopamine signaling, which seemingly contradicts this observed effect. To this end, the study aimed to clarify the mechanism of caffeine neuroprotection in vivo when excess dopamine is present. Transgenic Caenorhabditis elegans (UA57) overproducing dopamine was exposed to caffeine for 7 days and monitored by observing GFP-tagged dopaminergic (DA) neurons via fluorescence microscopy. Caffeine (10 mM) prevented neuronal cell loss in 96% of DA neurons, with a mean GFP intensity that is 40% higher than control (0.1% DMSO). To confirm if cAMP plays a role in the observed neuroprotection by caffeine, cAMP levels were elevated via forskolin (10 μM), an adenylyl cyclase activator. Forskolin (10 μM) exposure did not confer neuroprotection and was similar to control (0.1% DMSO) at the 7th day, suggesting that cAMP is not the sole secondary messenger utilized. Rotigotine (160 μM), a dopamine D2-like receptor (DOP2R) agonist, was not able to confer significant neuroprotection to the nematodes. This suggests that DOP2R activation is necessary but insufficient to mimic neuroprotection by caffeine. Lastly, co-administration of caffeine (10 mM) with olanzapine (160 μM), a DOP2R antagonist, eliminated neuroprotection. This suggests that the protective effect must involve both adenosine receptor antagonism and activation of DOP2Rs. Taken together, we show that caffeine protects DA neurons from dopamine-induced neurodegeneration and acts by modulating adenosine receptor-DOP2R interactions in C. elegans.